Pengaruh Tingkat Pengangguran Terbuka (TPT), Indeks Pembangunan Manusia (IPM) dan Tingkat Partisipasi Angkatan Kerja (TPAK) terhadap Kemiskinan di Indonesia - Purnama, Eka (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to analyze the effect of the Open Unemployment Rate (OUR), Human Development Index (HDI), and Labor Force Participation Rate (LFPR) on poverty in Indonesia. The study employs a quantitative approach using multiple linear regression analysis with cross-sectional data covering 38 provinces in Indonesia. Secondary data were obtained from the official publications of Statistics Indonesia (BPS). Poverty rate is used as the dependent variable, while OUR, HDI, and LFPR are employed as independent variables. The results show that the Open Unemployment Rate has a positive and significant effect on poverty, indicating that higher unemployment leads to an increase in the poverty rate. The Human Development Index has a negative and significant effect on poverty, suggesting that improvements in education, health, and living standards contribute to poverty reduction. Meanwhile, the Labor Force Participation Rate shows a positive and significant effect on poverty, indicating that increased labor force participation does not automatically reduce poverty when not accompanied by adequate employment opportunities and job quality. Simultaneously, OUR, HDI, and LFPR significantly affect poverty in Indonesia. These findings highlight the importance of strengthening job creation policies, improving the quality of human development, and enhancing labor market effectiveness as part of a comprehensive poverty alleviation strategy in Indonesia